2014
DOI: 10.1021/ic403148f
|View full text |Cite
|
Sign up to set email alerts
|

1,2,4-Triazolyl-Carboxylate-Based MOFs Incorporating Triangular Cu(II)-Hydroxo Clusters: Topological Metamorphosis and Magnetism

Abstract: Bifunctional 1,2,4-triazole-carboxylate ligands, an achiral 1,2,4-triazol-4-yl-acetic acid (trgly-H) and a chiral (d)-2-(1,2,4-triazol-4-yl)-propionic acid (d-trala-H), derived from the corresponding α-amino acid precursors revealed unique binding abilities in the construction of Cu(II)-coordination polymers composing discrete triangular [Cu3(μ3-OH)] clusters. A related series of MOFs, [Cu3(μ3-OH)(trgly)3(SO4)]·2H2O (1a), [Cu3(μ3-OH)(trgly)3(H2O)3]SO4·16H2O (1b), Cu3(μ3-OH)(d-trala)3(ClO4)0.5](ClO4)1.5·1.5H2O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 69 publications
0
34
0
Order By: Relevance
“…For 3, the χMT value is 0.36 cm 3 K mol −1 at 300 K, which is lower than the value expected for single high-spin Cu II ion (0.375 cm 3 mol -1 K, assuming g = 2.0). [61][62] The χMT value slowly decreases to 0.34 cm 3 K mol −1 at 15 K and then descends more sharply, reaching a value of 0.27 cm 3 K mol −1 at 1.8 K. It indicates a very weak antiferromagnetic behavior presented in the complex. The inverse magnetic susceptibility curve shows a linear behavior in 100−300 K range and can be fitted to the Curie−Weiss law, χ = C/(T − θ), yielding C = 0.37 cm 3 mol −1 K and θ = −2.24 K. The negative θ value for 3 also suggests an antiferromagnetic property, the same as 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…For 3, the χMT value is 0.36 cm 3 K mol −1 at 300 K, which is lower than the value expected for single high-spin Cu II ion (0.375 cm 3 mol -1 K, assuming g = 2.0). [61][62] The χMT value slowly decreases to 0.34 cm 3 K mol −1 at 15 K and then descends more sharply, reaching a value of 0.27 cm 3 K mol −1 at 1.8 K. It indicates a very weak antiferromagnetic behavior presented in the complex. The inverse magnetic susceptibility curve shows a linear behavior in 100−300 K range and can be fitted to the Curie−Weiss law, χ = C/(T − θ), yielding C = 0.37 cm 3 mol −1 K and θ = −2.24 K. The negative θ value for 3 also suggests an antiferromagnetic property, the same as 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…[69] Recently, Wang et al firstly reported a rigid copper thiolate cluster-assembled material (Cu 12 bpy, bpy = 4,4'-bipyridine). [74] They demonstrated an increase in the content of dense copper of copper azide composites, which contributed to the high output energy of copper azide-based explosives.…”
Section: Framework Cu Species In Mofsmentioning
confidence: 99%
“…Besides the presence of nodal Cu-core in MOFs, specific framework functionalities can also be utilised to incorporate or encapsulate extra-framework Cu species. [74] Chapman et al have functionalised NU-1000 (a Zr-based MOF) with Cu through atomic layer deposition. [75] The local structure of the supported Cu species was probed by combining pair distribution function analysis and difference envelope density analysis of the in situ synchrotron-based X-ray scattering data (see Figure 9).…”
Section: Extra-framework Cu Species In Mofsmentioning
confidence: 99%
“…Among these factors, the organic ligand plays an important role because changing it can control and adjust the coordination frameworks and topologies [16][17][18][19]. Since a carboxylate group can bridge metal ions and lock their position into M-O-C clusters, which can act as rigid entities and improve the stabilization of the compounds, di and polycarboxylic acids are widely used as bridging ligands to construct coordination frameworks with versatile structures [20][21][22][23][24][25]. As a member of dicarboxylate ligands, 4 nitrophthalic acid (H 2 NPTA) contains four potential metal binding sites, which can yield the formation of a coordination poly mer through multiple bonding interactions, adopt dif ferent conformations and coordination modes, and provide abundant structural motifs.…”
Section: Introductionmentioning
confidence: 99%